Revitalisasi Tradisi Ponan sebagai Strategi Meningkatkan Pendapatan Asli Desa Melalui Kearifan Lokal :Pengabdian Masyarakat - Sudrajat Martadinata; Tri Satriawansyah (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2024)
This community service aims to design a strategy for the revitalization of the Ponan Tradition in Poto Village, Sumbawa, West Nusa Tenggara, as an effort to preserve culture and empower the community's economy. The Ponan tradition, a traditional ceremony that is rich in noble values, has the potential to be developed as a cultural tourist attraction and source of genuine village income. However, the condition of the existing PADes is still poor and the lack of innovation in managing traditions is a challenge that needs to be overcome. This program focuses on several main activities, namely: preparing a comprehensive and sustainable Ponan Tradition revitalization strategy, increasing community understanding and appreciation of cultural values ​​and local wisdom, establishing creative economic business units based on the Ponan Tradition, increasing Village Village through the development of culture-based tourism, and development of collaborative networks between village government, community, academics and the private sector. Innovation and creativity are applied in tourism product development, event management and marketing, by utilizing digital technology and local wisdom. The expected benefits of this program include: increasing community understanding and appreciation of the Ponan Tradition, the formation of creative economic business units, increasing PADes, building cooperation networks, and realizing sustainable village development. Through the revitalization of the Ponan Tradition, it is hoped that the welfare of the people of Poto Village can increase and this tradition can be preserved for future generations.